2022
DOI: 10.3390/ijms232012619
|View full text |Cite
|
Sign up to set email alerts
|

Restriction of Flaviviruses by an Interferon-Stimulated Gene SHFL/C19orf66

Abstract: Flaviviruses (the genus Flavivirus of the Flaviviridae family) include many arthropod-borne viruses, often causing life-threatening diseases in humans, such as hemorrhaging and encephalitis. Although the flaviviruses have a significant clinical impact, it has become apparent that flavivirus replication is restricted by cellular factors induced by the interferon (IFN) response, which are called IFN-stimulated genes (ISGs). SHFL (shiftless antiviral inhibitor of ribosomal frameshifting) is a novel ISG that inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…25 Many studies have reported that ISGs play critical roles to restrict ZIKV replication. [27][28][29][30][31][32][33] For example, Viperin has been reported…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Many studies have reported that ISGs play critical roles to restrict ZIKV replication. [27][28][29][30][31][32][33] For example, Viperin has been reported…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that ISGs play critical roles to restrict ZIKV replication 27–33 . For example, Viperin has been reported to inhibit ZIKV RNA translation by activating ribosome collision‐dependent pathway 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Flaviviruses are a genus of viruses belonging to the Flaviviridae family [125]. Their genome has the form of positive-sense single-stranded RNA and is enclosed in an enveloped capsid.…”
Section: Mcl-1 In Flavivirus Infectionmentioning
confidence: 99%
“…The shiftless antiviral inhibitor of ribosomal frameshifting gene (SHFL), also known as RyDEN, C19orf66, or IRAV (the murine ortholog, Shfl), is an ISG that inhibits viral replication via binding to nucleic acids and inhibiting the virus‐programmed ribosomal frameshifting required for translation by many RNA viruses, and encodes a protein composed of 291 amino acids 8,9 . An increasing number of studies suggests that SHFL exhibits broad‐spectrum antiviral activity through a variety of underlying molecular mechanisms, including arboviruses (Dengue virus/DENV, Japanese encephalitis virus/JEV, Zika virus/ZIKV, West Nile virus/WNV, and Chikungunya virus/CHIKV), human immunodeficiency virus (HIV), Kaposi's sarcoma‐associated herpesvirus (KSHV), hepatitis C virus (HCV), and porcine epidemic diarrhea virus 10–20 . It has been established that there are two isoforms of SHFL arising from alternative splicing, including the long form, which comprises 291 amino acids, and the short form, namely SHFL‐209, is comprised of only 36 amino acids (164–199), lacking a beta‐strand present in SHFL 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 An increasing number of studies suggests that SHFL exhibits broad-spectrum antiviral activity through a variety of underlying molecular mechanisms, including arboviruses (Dengue virus/DENV, Japanese encephalitis virus/JEV, Zika virus/ZIKV, West Nile virus/WNV, and Chikungunya virus/ CHIKV), human immunodeficiency virus (HIV), Kaposi's sarcomaassociated herpesvirus (KSHV), hepatitis C virus (HCV), and porcine epidemic diarrhea virus. [10][11][12][13][14][15][16][17][18][19][20] It has been established that there are two isoforms of SHFL arising from alternative splicing, including the long form, which comprises 291 amino acids, and the short form, namely SHFL-209, is comprised of only 36 amino acids (164-199), lacking a beta-strand present in SHFL. 10,11 The long-form SHFL protein contains eight alpha-helixes, seven beta-strands, a zincribbon domain (112-135), nuclear localization signal (NLS) (121-137), nuclear export signal (NES) (261-269), and coiled-coil motif (261-285).…”
Section: Introductionmentioning
confidence: 99%